Efficacy Of Herbal Binder In Aflatoxin B1 Induced Toxicity On Haematological Profile In Wistar Rats - A., Prajapati; Verma, Y.; Swamy, M.; Dubey, A. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was conducted in forty eight male wistar rats to evaluate the efficacy of herbal binder on AFB1 induced toxicity on haematological profile. Aflatoxin adversely affected haematological profile. Administration of AFB1 was found to be immunosuppressive, leading to significant reduction in total erythrocyte count, haemoglobin concentration, packed cell volume and lymphocyte percent. There was significant increase in total leukocyte count and neutrophil in rats of group II as compared to the control group animals. However supplementation of herbal binder diminished the toxicity produced by aflatoxin administration in rats.